DAMPAK PANDEMI COVID-19 TERHADAP USAHA ATK DAN FOTOCOPY DI SEPAKAT 2 (WILAYAH KOTA PONTIANAK) - Laura, Angela; Witarsa, Witarsa; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The purpose of this study is to assess how the Covid-19 epidemic has affected stationery and copying shops in Sepakat 2 (Pontianak city). Case studies, a kind of qualitative research, are used in this investigation. Researchers in this research gathered information from ATK and photocopying business players in Sepakat 2 (Pontianak city region) via in-person observation, interviews, and document analysis. Four representatives from ATK and Photocopy participated as interviewees for this research. Reducing data, presenting data, and generating conclusions are all parts of data analysis. Source triangulation for testing validity. Based on the data shown here, it seems that the ATK and Photocopy companies experienced a drop in demand for their products and services, a reduction in operating hours, and a loss of revenue as a consequence of the Covid-19 epidemic. There was a significant drop in revenue (turnover) for stationery and copying shops during the Covid-19 epidemic, and although business has picked up again since then, it still isn't back to pre-pandemic levels.